Lack of Mutational Hot Spots during Decitabine-Mediated HIV-1 Mutagenesis - Rawson, Jonathan M. O. (Antimicrob Agents Chemother, 2015)
Decitabine has previously been shown to induce lethal mutagenesis of human immunodeficiency virus type 1 (HIV-1). However, the factors that determine the susceptibilities of individual sequence positions in HIV-1 to decitabine have not yet been defined. To investigate this, we performed Illumina high-throughput sequencing of multiple amplicons prepared from proviral DNA that was recovered from decitabine-treated cells infected with HIV-1. We found that decitabine induced an ≈4.1-fold increase in the total mutation frequency of HIV-1, primarily due to a striking ≈155-fold increase in the G-to-C transversion frequency. Intriguingly, decitabine also led to an ≈29-fold increase in the C-to-G transversion frequency. G-to-C frequencies varied substantially (up to ≈80-fold) depending upon sequence position, but surprisingly, mutational hot spots (defined as upper outliers within the mutation frequency distribution) were not observed. We further found that every single guanine position examined was significantly susceptible to the mutagenic effects of decitabine. Taken together, these observations demonstrate for the first time that decitabine-mediated HIV-1 mutagenesis is promiscuous and occurs in the absence of a clear bias for mutational hot spots. These data imply that decitabine-mediated G-to-C mutagenesis is a highly effective antiviral mechanism for extinguishing HIV-1 infectivity.